A Review of Aphroditic Plants and Physical Activity on Testosterone Concentrations - S Heidarzadeh; MA Azarbayjani; H Matinhomaee; M Hedayati (Institue of Medicinal Plants, ACECR, 2018)
Despite of many studies indicated that use of synthetic drugs to improve the concentration of testosterone in achieving secondary traits in men as a result, increased muscle mass and strength in this group, However, it has been shown that the use of these drugs in men causes physical and hormonal disorder and reduces performance when not in use. On the other hand, due to the clarification of side effects and the reporting of harmful effects of synthetic drugs, it has been shown that Plant products and exercise as substitute or complementary synthetic drugs can be a good alternative to the effects of kinetics and therefore it can be recommended the supplementation of herbals to coaches and athletes. Therefore, in this review, in addition to study of mechanisms of the increasing testosterone concentrations, we examine the effects of the use of some herbal supplements as well as physical activity.